China road a journey into the future of a rising power - Gifford, Rob (Random House Trade Paperbacks, 2008)
Route 312 is the Chinese Route 66. It flows 3,000 miles, passing through the factory towns of the coastal areas, through the rural heart of China, then up into the Gobi Desert, where it merges with the Old Silk Road. The highway witnesses every part of the social and economic revolution that is turning China upside down. In this surprising book, radio journalist Rob Gifford, a fluent Mandarin speaker, takes Route 312 from its start in the boomtown of Shanghai to its end on the border with Kazakhstan. Gifford reveals the rich mosaic of modern Chinese life in all its contradictions, as he poses the crucial questions that all of us are asking about China: Will it really be the next global superpower? Is it as solid and as powerful as it looks from the outside? And who are the ordinary Chinese people, to whom the 21st century is supposed to belong? --From publisher description.